39.4k views
4 votes
F(x)=

2

x

2



5

x



8

2x

2

−5x−8

g

(

x

)

=

g(x)=







5

x

+

4

−5x+4

Find:

(

g



f

)

(

x

)

Find: (g∘f)(x)

User Rozumir
by
4.6k points

1 Answer

6 votes

Answer:


(g\ o\ f)(x) = -10x^2 + 25x + 44

Explanation:

Given


f(x) = 2x^2 - 5x - 8


g(x) = -5x+4

Required


Find:\ (g\ o\ f)(x)

In functions;


(g\ o\ f)(x) = g(f(x))

Substitute
f(x) = 2x^2 - 5x - 8 in
(g\ o\ f)(x) = g(f(x))


(g\ o\ f)(x) = g(f(2x^2 - 5x - 8))

Solving for
g(f(2x^2 - 5x - 8))

If
g(x) = -5x+4

then


g(f(2x^2 - 5x - 8)) = -5(2x^2 - 5x - 8) + 4

Open Bracket


g(f(2x^2 - 5x - 8)) = -10x^2 + 25x + 40 + 4


g(f(2x^2 - 5x - 8)) = -10x^2 + 25x + 44

Recall that:


(g\ o\ f)(x) = g(f(2x^2 - 5x - 8))

This implies that


(g\ o\ f)(x) = -10x^2 + 25x + 44

User Dalton Whyte
by
4.6k points